Periodicity , positivity and stability of solutions for some delay dynamic equations using the fixed point technique - Daira Ibtissem (My University, 2024)
Abstract This thesis focuses on examining the periodicity, positivity, and stability of solutions for specific delay dynamic equations on time scales. To achieve this, we initially introduce fundamental concepts pertaining to functional analysis, fixed point theory, and time scale calculus. Subsequently, we enhance the comprehensiveness of previously studied delay differential equations by reformulating them to be applicable on any time scale. Additionally, we carefully select a suitable fixed point theorem that yields improved outcomes under reasonable conditions. better understanding, we supplemented the results with an example in the time scale. Mathematics Subject Classification : 34K13, 34K20, 34K30, 34K40, 45D05, 45J05, 47H10. ================ الملخص في هذه الأطروحة نقوم بدراسة الدورية والإيجابية والاستقرار لحلول المعادلات الديناميكية ذات تأخير المعرفة على ازمنة سلمية. من أجل تحقيق هذا الهدف، نقدم في البداية المفاهيم الأساسية المتعلقة بالتحليل الدالي، ونظريات النقطة الثابتةوالحساب على الازمةالسلمية. بعد ذلك، نهتمبدراسة المعادلات التفاضلية ذاتتأخير التي تمت دراستها سابقًا من خلال إعادة دراستها بطريقة تجعلها قابلة للتطبيق على أيةازمةسلمية. بالإضافة إلى ذلك، نختار بعناية نظرية النقطة الثابتة المناسبة التي تعطي نتائج محسنة بشروط معقولة.نقوم بتوضيح النتائج المتحصل عليها من خلال اعطاء امثلة علىازمةسلمية. الكلمات المفتاحية: . =========== Résumé Cette thèse se concentre sur l'examen de la périodicité, de la positivité et de la stabilité des solutions pour des équations dynamiques à retard spécifiques sur des échelles de temps. Pour y parvenir, nous introduisons d'abord des concepts fondamentaux relatifs à l'analyse fonctionnelle, à la théorie du point fixe et au calcul d'échelle de temps. Par la suite, nous améliorons l'exhaustivité des équations différentielles à retard étudiées précédemment en les reformulant pour qu'elles soient applicables à n'importe quelle échelle de temps. De plus, nous sélectionnons soigneusement un théorème de point fixe approprié qui donne de meilleurs résultats dans des conditions raisonnables. Pour une meilleure compréhension, nous avons complété les résultats par un exemple dans l'échelle de temps.
Keywords: Fixed point theory; periodicity; positivity; stability; time scales; delay dynamic equations.; نظريات النقطة الثابتة، الدورية ، الإيجابية، الاستقرار، الازمةالسلمية، المعادلات الديناميكية ذاتتأخير; Théorie du point fixe; périodicité; positivité; stabilité; échelles de temps; équations dynamiques à retard. Classification des matières mathématiques : 34K13; 34K20; 34K30; 34K40; 45D05; 45J05; 47H10.